Six species of Fissidens Hedw. (Fissidentaceae; Dicranales; Bryopsida), additions to Bryoflora of Andhra Pradesh - Sreenath, Ananthaneni; Rao, Boyina Ravi Prasad (International Journal of Scientific Research in Biological Sciences, 2022)
Six species of Fissidens Hedw., viz., F. bilaspurense Gangulee, F. elongatus Mitt., F. laxitextus Broth. ex Gangulee, F. polysetulus Mull. Hall. ex Nork. & Gangulee and F. subpalmatus Mull. Hall. and Fissidens titalyanus Mull. Hall. are collected from different localities in Andhra Pradesh are being reported as new distributional records to the state, of which Fissidens bilaspurense Gangulee, F. elongatus Mitt., F. laxitextus Broth. ex Gangulee, are recorded first time from Southern Peninsular India, India.